Evaluation of cytomegalovirus prophylaxis in low and intermediate risk kidney transplant recipients receiving lymphocyte‐depleting induction. Issue 4 (18th February 2021) - Stamps, Hillary; Linder, Kristin; O'Sullivan, David M.; Serrano, Oscar K.; Rochon, Caroline; Ebcioglu, Zeynep; Singh, Joseph; Ye, Xiaoyi; Tremaglio, Joseph; Sheiner, Patricia; Cheema, Faiqa; Kutzler, Heather L.
Abstract: Cytomegalovirus (CMV) is a significant cause of morbidity in kidney transplant recipients (KTR). Historically at our institution, KTR with low and intermediate CMV risk received 6 months of valganciclovir if they received lymphocyte depleting induction therapy. This study evaluates choice and duration of CMV prophylaxis based on donor (D) and recipient (R) CMV serostatus and the incidence of post‐transplant CMV viremia in low (D‐/R‐) and intermediate (R+) risk KTR receiving lymphocyte‐depleting induction therapy. A protocol utilizing valacyclovir for 3 months for D‐/R‐ and valganciclovir for 3 months for R+ was evaluated. Adult D‐/R‐ and R+ KTR receiving anti‐thymocyte globulin, rabbit or alemtuzumab induction from 8/20/2016 to 9/30/2018 were evaluated through 1 year post‐transplant. Patients were excluded if their CMV serostatus was D+/R‐, received a multi‐organ transplant, or received basiliximab. Seventy‐seven subjects met the inclusion criteria: 25 D‐/R‐ (4 historic group, 21 experimental group) and 52 R+ (31 historic, 21 experimental). No D‐/R‐ patients experienced CMV viremia. Among the R+ historic and experimental groups, there was no significant difference in viremia incidence (35.5% vs 52.4%; P = .573). Of these cases, the peak viral load was similar between the groups (median [IQR], 67 [<200‐444] vs <50 [<50‐217]; P = .711), and there was no difference in the incidence of CMV syndrome (16.1% vs 14.3%; P = 1.000) or CMV related hospitalization (12.9% vs 14.3%; P = 1.000). No patient experienced tissue invasive disease. These results suggest limiting valganciclovir exposure may be possible in low and intermediate risk KTR receiving lymphocyte‐depleting induction therapy with no apparent impact on CMV‐related outcomes.